Growth resilience of conifer species decreases with early, long‐lasting and intense droughts but cannot be explained by hydraulic traits. (7th June 2022) - Song, Yanjun; Sterck, Frank; Sass‐Klaassen, Ute; Li, Chenxuan; Poorter, Lourens
Abstract: Drought events may reduce growth and survival of conifer trees. The effects of the intensity and timing of drought on the growth resilience, including growth reductions during drought and recovery of growth after drought, remain, however, highly uncertain. Growth resilience of 20 conifer species to 11 dry years was compared in a common garden experiment. We assessed (a) the relationships among growth resistance, recovery and resilience, (b) the impacts of different drought dimensions (intensity, onset and length) on resistance and (c) the underlying mechanisms in terms of growth potential and hydraulic traits. Droughts led to 22% reduction in stem growth for 85% of species, but most species (85%) were resilient due to high recovery. Growth resistance decreased with an early onset of drought (significant for 55% of species), and longer‐lasting (35%) and intense droughts (60%). While fast‐growing species and slow‐growing species were similar in resistance and recovery, fast‐growing species were more resilient. Unexpectedly, resilience could not be explained by hydraulic traits, possibly because the species grew on poor sandy soils and were acclimated to drought with large hydraulic safety margins. Synthesis . Our study shows that in a mild maritime climate almost all conifer species are resilient to drought, and that putative hydraulic traits may be less important here for growth resilience. It also highlights the importance of addressing multiple dimensions of drought, that is, timing, duration and severity, to predict species responses to climate change. Abstract : The impact of multiple dimensions of drought on tree growth resilience remains highly uncertain. Droughts led to 22% reduction in stem growth for 85% of conifer species. Growth resistance decreased with tree size (significant for 40% of species), early onset of drought (55%), longer‐lasting (35%) and intense (60%) droughts. It highlights the importance of addressing multiple dimensions of drought to predict growth responses to climate change.